Heat capacities and thermodynamics of formation of ε-Keggin MAl12 Selenates (M = Al(III), Ga(III), or Ge(IV)). (October 2015) - Reusser, Dana; Schliesser, Jacob; Woodfield, Brian F.; Navrotsky, Alexandra
Highlights: Calorimetry was used to measure Δ ds H for a germanium – substituted Al13 selenate. The enthalpies, Δ f H ° and Δ f, ox H, were determined for this GeAl12 selenate. Heat capacities were measured on the MAl12 selenates, M = Al(III), Ga(III) or Ge(IV). Standard entropies and free energies were determined for these MAl12 selenates. Energetics of AlAl12 and GaAl12 were similar; GeAl12 was found to be less stable. Abstract: We report enthalpies of formation from the elements and oxides, Δ f H °  = −(22, 673.44 ± 30.19)  kJ · mol - 1 and Δ f, ox H  = −(869.68 ± 28.75)  kJ · mol - 1, for [GeO4 Al12 (OH)24 (H2 O)12 ](SeO4 )4 ·12H2 O(cr) (GeAl12 ) measured using high temperature oxide-melt solution calorimetry. This material is the selenate salt of the germanium-substituted polynuclear Al 13 7 + ion in the ε-Keggin structure. We also report heat capacities from temperatures of (2 to 300) K on this GeAl12 selenate and its other heterometal substituted forms, Na[AlO4 Al12 (OH)24 (H2 O)12 ](SeO4 )4 ·12H2 O(cr) (AlAl12 ) and Na[GaO4 Al12 (OH)24 (H2 O)12 ](SeO4 )4 ·12H2 O(cr) (GaAl12 ), measured using a Quantum Design Physical Property Measurement System (PPMS). These measurements were used to calculate entropies and subsequently free energies of formation for these three materials. All three MAl12 selenates, where M = Al(III), Ga(III), or Ge(IV), have similar heat capacities from temperatures (2 to 300) K and similar characteristic Debye temperatures, ΘD, suggesting similar lattice vibrational densities of states.